Combination of honey supplementation and countermovement jumping exercise influence bone turnover markers in young males - Muhammad Imran Mohd Zuhri; Mohamed Mirza Dawlath Mohamed; Ooi, Foong Kiew; Nur Syamsina Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study investigated the combined effects of Tualang Honey (TH) and countermovement jumping (CJ) exercise for 6 weeks on bone speed of sound (SOS), bone turnover markers, and maximum jumping height in young males. Forty participants aged between 18-24 years old were randomly assigned into four groups, i.e. control (C), supplementation of TH (H), CJ exercise (J), and combined TH supplementation, and CJ exercise (JH) groups. Participants in the J and JH groups were required to jump for 2 sessions/day, 3 alternated days/week for 6 weeks. Participants in the H and JH groups consumed 20 g/day of TH for 6 weeks. Bone SOS of the participants’ leg was measured at pre- and post-tests, and it was found that there were no significant differences in participants’ bone SOS in all groups. Blood samples were analysed for determining the concentration of serum alkaline phosphatase (ALP) and serum C-terminal telopeptide of type-1 collagen (1CTP). The JH group showed a 56.3% reduction in serum 1CTP and was significantly lower (p <0.01) than the C group. A 7.66% reduction of ALP was observed in the JH group. Maximum jumping height was significantly greater (p <0.05) in post-tests compared to pre-tests in the H and JH groups. In addition, there was a significantly greater maximum jumping height (p <0.05) in the JH group compared to the C group in post-tests. In conclusion, the combination of TH with CJ exercise could significantly increase maximum jumping height compared to the control and this combination influence bone turnover markers in young males.